Performance Enhancement and IoT Based Controlling for Smart Home - Kayalvizhi, S; Pradeep Kumar, K; Sai Akhil, S; Vinay, T (International Journal of Engineering and Technology, 2018)
Automation is becoming vastly used due to its numerous advantages. Building automation refers to control any type of building appliances by using mobile network or the local area network. It is a process of operating or controlling electronic appliances by reducing the basic human requirments.